Nepalese consumers' perception on online shopping challenges and its managerial solution - Niranjan Devkota; Shashwat Dhungana; Seeprata Parajuli; Udbodh Bhandari; Udaya Raj Paudel (Northern Negros State College of Science and Technology (NONESCOST), 2021)
Though the trend for online shopping is increasing still the practice of online shopping in Nepal is at a primitive stage. The study aims to identify Nepalese consumers' perception of online shopping, challenges, and managerial solution towards online shopping in Kathmandu, Nepal. Descriptive research design was used to describe the customers' perception of buying online goods. The study was targeted towards those people living in Kathmandu valley who are mainly active on their mobile phones and have bought any goods or services from online platforms. Using purposive sampling, a total of 403 respondents were interviewed with the help of a structured questionnaire using the KOBO Collect Toolbox. This study finds that 66.0% of people believe that there are different challenges while shopping online. A maximum number of respondents (i.e. 41.6%) feel products not matching as shown on the website is the most common faced challenge while doing online shopping. Similarly, choose poor quality products as they could not figure out the difference in online application sites (32.12%), timely delivery of the products (10.95%), hidden costs (8.75%), and long procedures (6.57%) are other challenges that the respondents' responded. 86.05% of the respondents feel the problems related to online shopping through mobile applications can be managed. Respondents (43.56%) believe that most of the problems related to online shopping through mobile applications can be solved by selling high-quality products that satisfy the customers' needs by looking online market, selling high-quality goods and services, the safe payment system through a mobile application, strict rules and regulations on online shopping, online shopping environment, managing delivery time, and receiving damaged products at the end of the day can promote online shopping among the customers. Sellers' positive attitude and behavior can help online shopping market promotion in the market in Nepal.